Myocardial morphology in hypertrophic cardiomyopathy: the current state of the problem - A. A. Balabai (Zaporožskij Medicinskij Žurnal)
The objective. Based on the modern sources of scientific data to analyze the morphological features of the myocardium in hypertrophic cardiomyopathy.